Caudate and cerebellar involvement in altered P2 and P3 components of GO/NoGO evoked potentials in children with attention‐deficit/hyperactivity disorder. (5th April 2021) - Zarka, David; Cebolla, Anna Maria; Cevallos, Carlos; Palmero‐Soler, Ernesto; Dan, Bernard; Cheron, Guy
Abstract: Previous studies showed reduced activity of the anterior cingulate cortex (ACC) and supplementary motor area during inhibition in children with attention‐deficit/hyperactivity disorder (ADHD). This study aimed to investigate deep brain generators underlying alterations of evoked potential components triggered by visual GO/NoGO tasks in children with ADHD compared with typically developing children (TDC). Standardized weighted low‐resolution electromagnetic tomography (swLORETA) source analysis showed that lower GO‐P3 component in children with ADHD was explained not only by a reduced contribution of the frontal areas but also by a stronger contribution of the anterior part of the caudate nucleus in these children compared with TDC. While the reduction of the NoGO‐P3 component in children with ADHD was essentially explained by a reduced contribution of the dorsal ACC, the higher NoGO‐P2 amplitude in these children was concomitant to the reduced contribution of the dorsolateral prefrontal cortex, the insula, and the cerebellum. These data corroborate previous findings showed by fMRI studies and offered insight relative to the precise time‐related contribution of the caudate nucleus and the cerebellum during the automatic feature of inhibition processes in children with ADHD. These results were discussed regarding the involvement of the fronto‐basal ganglia and fronto‐cerebellum networks in inhibition and attention alterations in ADHD. Abstract : Lower GO‐P3 component in children with ADHD was explained not only by a reduced contribution of the frontal areas but also by a stronger contribution of the anterior part of the caudate nucleus in these children compared with TDC. The reduction of the NoGO‐P3 component in children with ADHD was essentially explained by a reduced contribution of the dorsal anterior cingulate cortex, the higher NoGO‐P2 amplitude in these children was concomitant to the reduced contribution of the dorsolateral prefrontal cortex, the insula, and the cerebellum. These data offered insight relative to the precise time‐related contribution of the caudate nucleus and the cerebellum during the automatic feature of inhibition processes in children with ADHD.